ANALYSIS OF THE WAGE SYSTEM FOR BILI DROE BAG WEAVING CRAFTSMEN IN THE PERSPECTIVE OF IJARAH 'ALA AL-AMAL CONTRACT - Zakia Auliani (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2019)
Usually, the determination of wages in each business is different, it depends on the policies applied by the business owner, such as the determination of wages in bili droe bag woven craftsmen in Gampong Lampanah Tunong, namely wages paid after the woven products are sold. The purpose of this research is to find out How the wage determination system on bili droe bag woven craftsmen, How the influence of wages on the effectiveness of the work of the bili droe bag woven craftsmen, And How the wage practices of bili droe bag woven craftsmen in Gampong Lampanah Tunong Indrapuri District Aceh Besar Regency are reviewed according to the perspective of the Ijarah 'Ala Al-Amal contract. In this study the authors used qualitative research methods and used an empirical normative approach. The results showed that the wage system applied to the woven bili droe bag business in Lampanah Tunong Gampong, Indrapuri District is a wage given after the woven product is sold, where there is no clear time provision when the product is sold. The wages carried out in this business also do not use a contract that binds it, but as if an agreement (contract) has occurred. ). The wage system applied is not in accordance with the perspective of the ijarah 'ala al-amal contract, where in practice the Shighat contract is not clear. In a contract if it does not fulfil the conditions for the validity of the contract, then the contract becomes fasid (void).